Advanced injectable micro-scaffolds for modular bone tissue engineering - Bjørge, Isabel Marinho Carvalho (2024)
Structure and organization are key aspects of the native tissue environment, which ultimately condition cell fate. Engineered geometrical and topographical cues appear as attractive options to control and guide cell behavior, yet such strategies are limited to a 2-dimensional approach, which differs from the native cell environment. Physically tuned microcarriers appear as attractive vehicles for cell-based tissue engineering strategies aiming to modulate this 3D environment, but also as vehicles for cell-free applications. On the geometry side, the varying surface area to volume ratio of designed spheroidal hydrogel particles with adjustable circularity was proven to impact drug release and cell viability, demonstrating its applicability for drug delivery or as cell encapsulation platforms. On the topography side, the developed quasi-3D sandwich culture model, enabling both ventral and dorsal cell surface stimulation, allowed to study the effect of grooved surface topography in a simultaneous and independent manner on two cell sides. Here, the pivotal role of initial cell-biomaterial contact on cellular alignment was highlighted, providing important insights for tissue engineering strategies aiming to guide cellular response through mechanotransduction approaches. In turn, 3D disc-shaped microcarriers featuring nanogrooved surface topography (topodiscs) were designed and produced, aiming to be applied as a bottom-up cell-mediated strategy. Applied to bone tissue engineering, topodiscs were shown to enhance cell proliferation and direct the formation of bone-like aggregates, even in the absence of osteoinductive factors. When combined with co-culture of stem/stromal cells and endothelial cells within liquefied core capsules, topodiscs demonstrated great potential in not only directing osteogenic, but also in the achieving a prevascularized construct. Taken together, our studies highlight the importance of physical cues in regenerative medicine strategies and illustrate how achieving a functional histoarchitecture may depend on a combination of fine-tuned geometrically shaped microcarriers presenting intricately tailored topographical cues.